Association of the methionine sulfoxide reductase A rs10903323 gene polymorphism with cardiovascular disease in patients with rheumatoid arthritis - García-Bermúdez, M; López-Mejías, R; González-Juanatey, C; Castañeda, S; Miranda-Filloy, JA; Blanco, R; Fernández-Gutiérrez, B; Balsa, A; González-Álvaro, I; Gómez-Vaquero, C; Llorca, J; Martín, J; et al. (Scandinavian journal of rheumatology, 2012)
Objective: The methionine sulfoxide reductase A (MSRA) gene is related to oxidative stress that has been involved in the susceptibility to rheumatoid arthritis (RA) in genome-wide pathway analysis and replication studies. The aim of the present study was to determine whether the MSRA gene is implicated in susceptibility to cardiovascular (CV) disease in RA patients. Methods: A total of 1302 patients fulfilling the 1987 American College of Rheumatism classification criteria for RA were genotyped for the MSRA rs10903323 (G/A) polymorphism. Two hundred and thirty-three (17.9%) patients experienced CV events. Human leucocyte antigen (HLA)-DRB1 genotyping was performed using molecular-based methods. Multiple logistic regression models were constructed with adjustments for gender, age at RA diagnosis, follow-up, rheumatoid shared epitope, and traditional CV risk as potential confounders. Results: There were no statistically significant differences in the allele or genotype frequencies for the MSRA rs10903323 polymorphism between RA patients who experienced CV events and those who did not. However, an adjusted logistic regression model disclosed that the minor allele G yielded a marginally significant increased risk of CV events in this series of patients with RA [p = 0.05, odds ratio (OR) 1.68, 95% confidence interval (CI) 1.00-2.85]. When the logistic regression model was adjusted for anti-cyclic citrullinated peptide (anti-CCP) antibody status instead of for shared epitope, an increased risk of having ischaemic heart disease was found in patients carrying the minor allele G (p = 0.04, OR 2.00, 95% CI 1.03-3.88). Conclusion: The MSRA rs10903323 gene polymorphism may be implicated in the increased risk to develop CV events, in particular ischaemic heart disease, observed in RA patients.